2002
DOI: 10.1079/phn2002388
|View full text |Cite
|
Sign up to set email alerts
|

Measuring food intake in studies of obesity

Abstract: The problem of how to measure habitual food intake in studies of obesity remains an enigma in nutritional research. The existence of obesity-specific underreporting was rather controversial until the advent of the doubly labelled water technique gave credence to previously anecdotal evidence that such a bias does in fact exist. This paper reviews a number of issues relevant to interpreting dietary data in studies involving obesity. Topics covered include: participation biases, normative biases, importance of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 19 publications
6
101
1
1
Order By: Relevance
“…In general, the studies show a tendency to an increase in underreporting with increasing age, the reason for that is thoroughly discussed in papers by Livingstone and Robson, 2000;Livingstone et al, 2004. Moreover, it was identified that obese adolescents and children underreported energy intake to a larger extent than normal-weight subjects, which is comparable to results found among adults (Lissner, 2002;Livingstone et al, 2004). Most of the validation studies were evaluating diet records with varying length.…”
Section: Selection Of Methodssupporting
confidence: 63%
“…In general, the studies show a tendency to an increase in underreporting with increasing age, the reason for that is thoroughly discussed in papers by Livingstone and Robson, 2000;Livingstone et al, 2004. Moreover, it was identified that obese adolescents and children underreported energy intake to a larger extent than normal-weight subjects, which is comparable to results found among adults (Lissner, 2002;Livingstone et al, 2004). Most of the validation studies were evaluating diet records with varying length.…”
Section: Selection Of Methodssupporting
confidence: 63%
“…It is commonly assumed that correction by energy-adjustment methods will in some way rectify the problem, without having to exclude data. 26,27 However, this may only be the case if under-reporting has occurred uniformly across foods at the level of the whole diet 26 and this is not likely to be so. Energy-adjustment methods cannot eliminate bias because of selective reporting of foods or beverages with the net effect being that nutrients are not under-reported in direct proportion to energy.…”
Section: Correction Of Measurement Errormentioning
confidence: 99%
“…22 Differences in error and biases between populations further highlight the need to validate dietary assessment methods in the population for which their use is intended. 26 Additional issues to consider include the purpose of the dietary assessment, subject burden, resources and time available to collect and analyze the dietary data, expertize required to interpret the data and whether group-or individual-level data is required.…”
Section: Correction Of Measurement Errormentioning
confidence: 99%
See 1 more Smart Citation
“…P for linear trend 5 0?001 Unfortunately, energy under-reporting is a common problem for the analysis of associations between diet and health outcomes, particularly BMI (16,17) . It has been shown that obese subjects tend to selectively under-or overestimate selected foods (16,17) . In the present study, prevalence of low energy reporting decreased with frequent soft drinks consumption.…”
Section: Discussionmentioning
confidence: 99%